Playing the "Game" of Transparency and Accountability: Non-elite Politics in Kyrgyzstan's Natural Resource Governance. Issue 2 (3rd March 2020) - Moldalieva, Janyl; Heathershaw, John
ABSTRACT: This article demonstrates the role of non-elites in the struggle for transparency and accountability in Kyrgyzstan's mining sector. Most existing accounts foreground elite strategies and political machines in the governance of post-Soviet societies. Drawing on recent anthropological work on post-Soviet politics and applying it critically to the literature on neopatrimonialism, this article sheds light on the adoption of political game strategies by community members (non-elites) to advance their interests and challenge elite dominance within the case study's mining communities. This finding responds to recent calls to interrogate the activities of non-elites at the margins of neopatrimonial contexts. The article advances a research agenda on how practices by non-elites shape the multiple meanings and enactments of transparency and accountability by elites in natural resource governance. It also points to the need to explore how and why "communities" exert their "agency" in governing natural resources within post-Soviet contexts.